The Cantabrian Fault at Sea. Low Magnitude Seismicity and Its Significance Within a Stable Setting - Fernández-Viejo, Gabriela; Llana-Fúnez, Sergio; Acevedo, Jorge; López-Fernández, Carlos (Frontiers in Earth Science, 2021)
The Cantabrian fault (CF) is a crustal-scale structure that cuts obliquely the western North Iberian Margin (NIM) for 160 km and continues onshore transecting the Cantabrian Mountains (CM) for another 150 km as the Ventaniella fault (VF). For most of its length inland, the fault system is aseismic, except for a 70 km long segment at its southern end. Within this segment, a gently north-dipping linear arrangement of earthquakes was interpreted as related to the intersection of a slightly oblique fault to VF with the basal thrust of the CM. In addition to earthquake nucleation along parts of its length, the CF–VF also stands out regionally as a major seismotectonic boundary, separating a seismically active area to the West from an essentially aseismic region to the East. Contrasting tectonothermal evolution in the crust on either side during the Mesozoic rifting may underlie the observed differences. On the other hand, the seismicity within the subsea segment is low magnitude, persistent, and understudied. The scarcity of the permanent seismic stations distribution in the area did not allow to establish more than a generalized consensus relating the offshore events to the submarine structure. A recent local seismic network monitored the area providing the highest accuracy information on the offshore events to date. Although the location of foci is partially challenged by the lack of recording stations from northern azimuths at sea, the observed pattern shows indeed a broad linear trend in the submarine domain in relation to the crustal-scale structure. Specifically, this study shows that the distribution of foci offshore display two preferential areas along the CF–VF within its southern crustal block. Considering the basement rock types and the deep architectural disposition of the margin crust, two possible explanations for the origin of the clusters are put forward in this contribution.